Aplicação do método da maturidade em paredes de concreto - Baum, Jean Lucas (Universidade do Vale do Rio dos Sinos, 2018)
A recurring concern, arising from the acceleration of the constructive processes, lies in the integrity and structural safety of the buildings, since the usual methods of control occur in a palliative way through destructive laboratory tests. Such tests often do not replicate the actual conditions and exposure to the weather encountered on site. In relation to the present need for alternative methods of production control in civil construction, this research presents the basis of the application of a process already known, but in little use in the country. The method in question is the estimation of the resistance at the early ages of concrete in Portland cement by the control of its temperature in situ. For this, correlations are made between the resistances tested in laboratory for a given trace and their relative reaction energy, monitored by reading the temperature in the concrete cast in construction site, in real time. Such a procedure is known as the Maturity Method and, in a non-destructively test, provides an estimation of the strength of concrete elements, providing crucial information for decision making regarding the removal of shoring, forms and concrete protrusion, for example. The analysis sequence, test periods and study parameters are determined by the American Society for Testing and Materials (ASTM International) standard through ASTM C 1074-11 Standard Practice for Estimating Concrete Strength by the Maturity Method. This study evaluated the application of the method in the constructive system of reinforced concrete support walls, by monitoring concreting cycles in order to record the temperature advance in the initial ages and to evaluate its applicability in situ. Through the application of ASTM C 1074, parallel to the measurements using specific instrumentation for measurement of maturity, it was possible to generate a correlation curve between temperature versus estimated resistance, creating a powerful tool of quality control and safety when combined with the methods already used in construction sites.
Keywords: Método da maturidade; Ensaios não destrutivos; Paredes de concreto; Maturity method; Non-destructive test; Concrete walls